Leonardo da Vinci: Scientist - Inventor - Artist - Museum of Science (2007)
[Dt.:] Gut aufbereitete und klar verständliche Einführung in das Werk Leonardos; Material für den Schulunterricht (für Lehrer und Schüler). - [Engl.:] Well produced and understandable introduction into life and work of Leonardo; material for teachers and students.